2010
DOI: 10.1002/app.30500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyethylene glycol on the performance of ultrahigh‐molecular‐weight polyethylene membranes

Abstract: Porous, flat membranes of ultrahigh-molecular-weight polyethylene (UHMWPE) were prepared by thermally induced phase separation, with mineral oil as a diluent and poly(ethylene glycol) with a weight-average molecular weight of 20,000 (PEG20000) as an additive. Through the control of the rheological behavior, crystallite size, and pore structure, the influential factors, including the diluent, poly(ethylene glycol) (PEG) content, and cooling rate, were investigated. The results suggested that PEG could decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The crystal structure of UHMWPE after extracting LP was characterized by XRD. As shown in Figure 3c, diffraction peaks around 21.6° and 23.9° were observed in all samples, corresponding to the orthorhombic (1 1 0) and (2 0 0) reflections of UHMWPE 28,29 . The crystallinities of UHMWPE porous films were still significantly higher than that of U 100 , indicating that the crystalline structure of UHMWPE was preserved after LP extraction.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The crystal structure of UHMWPE after extracting LP was characterized by XRD. As shown in Figure 3c, diffraction peaks around 21.6° and 23.9° were observed in all samples, corresponding to the orthorhombic (1 1 0) and (2 0 0) reflections of UHMWPE 28,29 . The crystallinities of UHMWPE porous films were still significantly higher than that of U 100 , indicating that the crystalline structure of UHMWPE was preserved after LP extraction.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 3c, diffraction peaks around 21.6 and 23.9 were observed in all samples, corresponding to the orthorhombic (1 1 0) and (2 0 0) reflections of UHMWPE. 28,29 The crystallinities of UHMWPE porous films were still significantly higher than that of U 100 , indicating that the crystalline structure of UHMWPE was preserved after LP extraction. The crystalline sizes of (1 1 0) and (2 0 0) diffraction planes of the samples after LP extraction increased firstly, and then decreased (Figure 3c).…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…Bulk hybridization modification has attracted increasing attention in the construction of an antifouling separation membrane . For example, some hydrophilic polymers, inorganic nanoparticles, and carbon nanotube materials are added as common modifiers to the separation membrane for antifouling modification to improve the overall hydrophilic and antifouling capacity of the separation membrane. , Polydopamine (PDA) particles (PDAPs) have been reported as a filler for constructing polymer composites because of their excellent properties (such as simplicity, self-polymerization, biocompatibility, and antioxidant properties). For example, Liang et al reported immobilized PDA/silver composite nanospheres on an oxidized sodium alginate sponge surface to fabricate antimicrobial sponges; Xiong et al prepared PDAP/poly­(vinylalcohol) biocomposites using different diameters of PDAPs as a filler; and Wang et al used PDA interfacial cross-linking on a porous supporting layer to fabricate thin-film nanocomposite membranes .…”
Section: Introductionmentioning
confidence: 99%
“…Porous UHMWPE membranes could be prepared by TIPS 5–7. In our previous study, the UHMWPE membrane8 and UHMWPE/SiO 2 hybrid membranes9, 10 with better permeability were prepared by TIPS. The main aim of our previous work was to improve membrane permeability through building the multi‐pore‐structure.…”
Section: Introductionmentioning
confidence: 99%